Otosclerosis Revisited - C V Srinivas (Bengal Journal of Otolaryngology and Head Neck Surgery, 2019)
Introduction: Otosclerosis usually manifests as a progressive conductive or mixed hearing loss occurring clinically to varying degrees in 0.5% - 1% of the general population. Stapedectomy /stapedotomy is the current treatment of choice for conductive component of Otosclerosis.